Professor Da Ruan’s Academic Activities with His Turkish Friends - Kahraman, Cengiz; Kabak, Özgür (Springer Berlin Heidelberg, 2013)
Prof. Cengiz Kahraman first contacted Prof. Da Ruan during the 5th International FLINS Conference, which was held in Gent, Belgium on September 16-18, 2002. Prof. Kahraman tells this contact period as follows: “When I informed Prof. Da Ruan about the problem, which prevented my travel to Belgium for FLINS 2002 conference, I was expecting an angry response from him. On the contrary, he understood my problem and said “It is no problem. We would like to see you at the next FLINS conference. I will mail the FLINS 2002 conference proceedings and materials to your postal address.” This was the first contact between Prof. Kahraman and Prof. Da Ruan.